The Effect of Digital Payment Innovation and Point Giving Marketing Strategy on Consumer Shopping Experience in the Culinary Industry - Anton Susilo; Emelia Rahmadany Putri Gami; Yohanis Resa Surentu; Eka Dian Hikmayani Jufri (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2024)
This study investigates the impact of digital payment innovation and point-of-sale marketing strategies on consumers' shopping experiences in the Yotta culinary industry. As companies strive to innovate and grow, understanding customer behavior and competitor capabilities becomes essential for achieving a competitive advantage. The study aims to: 1) Analyze the effect of digital payment innovation on consumer shopping experiences, 2) Assess the influence of point-of-sale marketing strategies, and 3) Examine the interaction between these factors. A descriptive analysis approach was utilized, with data collected from 35 questionnaires. The results indicate that digital payment innovation significantly affects consumer shopping experiences, with an average score of 35.80 and a standard deviation of 3.692. The point-of-sale marketing strategy also influences consumer experiences, reflected by an average score of 24.60 with a standard deviation of 2.746. The overall consumer shopping experience scored an average of 24.68 with a standard deviation of 2.598, suggesting that Yotta consumers are more inclined to choose digital payment options. The findings offer valuable insights for stakeholders aiming to enhance consumer satisfaction through innovative payment and marketing strategies.